TBC1D24 interacts with the v-ATPase and regulates intraorganellar pH in neurons - Sara Pepe; Davide Aprile; Enrico Castroflorio; Antonella Marte; Simone Giubbolini; Samir Hopestone; Anna Parsons; Tânia Soares; Fabio Benfenati; Peter L. Oliver; Anna Fassio (iScience)
Summary: The vacuolar ATPase (v-ATPase) is essential for acidification of intracellular organelles, including synaptic vesicles. Its activity is controlled by cycles of association and dissociation of the ATP hydrolysis (V1) and proton transport (V0) multi-protein subunits. Mutations in genes coding for both v-ATPase subunits and TBC1D24 cause neurodevelopmental disorders with overlapping syndromes; therefore, it is important to investigate their potentially interrelated functions. Here, we reveal that TBC1D24 interacts with the v-ATPase in the brain. Using a constitutive Tbc1d24 knockout mouse model, we observed accumulation of lysosomes and non-degraded lipid materials in neuronal tissue. In Tbc1d24 knockout neurons, we detected V1 mis-localization with increased pH at endo-lysosomal compartments and autophagy impairment. Furthermore, synaptic vesicles endocytosis and reacidification were impaired. Thus, we demonstrate that TBC1D24 is a positive regulator of v-ATPase activity in neurons suggesting that alteration of pH homeostasis could underlie disorders associated with TBC1D24 and the v-ATPase.